Work Motivation Affects the Performance of Health Workers - Mutmainah, Mutmainah; Vanchapo, Antonius Rino; Wawo, Balbina Antonelda Marled (Journal of World Future Medicine, Health and Nursing, 2023)
Work motivation as a driving force that causes a person to be willing and willing to direct the ability of energy and time in order to achieve goals and the performance of health workers serves as a benchmark for health services so it is necessary to study performance in order to maintain and even improve the quality of services Health workers have an important role as public health development. This literature review aims to determine the relationship between work motivation and the performance of puskesmas health workers. This type of research is literature review research, the articles used were obtained from PubMed and Google Scholar with articles published starting from 2016-2023. The number of journal articles was 10 articles analyzed. The results of the study showed that there was a relationship between work motivation and the puskesmas health workers. It can be interpreted that work motivation has a positive and significant effect on workforce performance, work motivation is depressed by the work enthusiasm of health workers in order to improve service quality.